استخدام وسيلة حمالة المفاتيح في تعليم المفردات لطلبة الصف الخامس بمدرسة الخير الابتدائية الإسلامية باراباي كاليمنتان الجنوبية - Ahla Rizqina; Ahmad Muradi; Ahmad Arifin (Sekolah Tinggi Agama Islam Al Washiliyah Barabai, 2024)
The researcher selected this title after identifying several challenges in the vocabulary learning of fifth-grade students at Al-Khair Barabai Integrated Islamic Elementary School. Some students had difficulty pronouncing, understanding, and memorizing Arabic vocabulary. Additionally, the Arabic teacher's reliance on books and the blackboard as teaching tools led to boredom and a lack of motivation among some students. This study focuses on the implementation of “gantungan kunci” media as a tool in teaching vocabulary to these students. The goal of the research is to assess the effectiveness of using “gantungan kunci”media in enhancing vocabulary learning. The study employed a quantitative approach with a quasi-experimental design, involving an experimental group and a control group. The research sample included class VB, which used “gantungan kunci” media, and class VA, which did not. The findings revealed that the post-test U-test results showed a Sign (2-Tailed) value of 0.00, which is below 0.05, with average scores of 85.23 for the experimental group and 58.92 for the control group. This indicates that the null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is accepted, confirming that the use of “gantungan kunci” media in vocabulary instruction is effective for fifth-grade students at Al-Khair Barabai Integrated Islamic Elementary School.